2003
DOI: 10.2337/diacare.26.5.1390
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Insulin Lispro Across the Human Placenta

Abstract: OBJECTIVE—Insulin lispro (Humalog), a human insulin analog, has a more rapid onset, earlier peak, and shorter duration of glucose lowering activity than regular human insulin. However, it is not known whether insulin lispro crosses the human placenta and reaches the fetus. Therefore, the objective of the present study was to examine whether insulin lispro crosses the placenta using the technique of perfusing a human placental lobule in vitro. RESEARCH DESIGN AND METHODS—Term human placentae from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(60 citation statements)
references
References 23 publications
1
56
0
3
Order By: Relevance
“…There is evidence that maternal leptin can cross the placenta and is a significant source of fetal leptin (Smith & Waddell 2003) but there is little transplacental transfer of insulin (Boskovic et al 2003). In our previous study, we showed that HF fetuses were hyperinsulinemic due to enhanced pancreatic insulin secretion (Srinivasan et al 2006 (Fig.…”
Section: Characterization Of Fetal Weights Leptin and Insulin Levelsmentioning
confidence: 86%
“…There is evidence that maternal leptin can cross the placenta and is a significant source of fetal leptin (Smith & Waddell 2003) but there is little transplacental transfer of insulin (Boskovic et al 2003). In our previous study, we showed that HF fetuses were hyperinsulinemic due to enhanced pancreatic insulin secretion (Srinivasan et al 2006 (Fig.…”
Section: Characterization Of Fetal Weights Leptin and Insulin Levelsmentioning
confidence: 86%
“…Insulin lispro was not detectable in cord blood when patients received continuous intravenous lispro and dextrose infusions intrapartum to assess placental transfer. However, in an in vitro perfusion study using human placentas, insulin lispro was found to cross the placenta at greater than normal therapeutic concentrations, with fetal perfusate concentration of lispro reaching up to 59% of maternal concentration (7). The mechanism of how the placenta handles therapeutic concentrations of lispro warrants further study.…”
Section: Rationale For the Use Of Non-immunogenic Insulins Duringmentioning
confidence: 95%
“…Maternal insulin does not cross the placenta unless it is bound to IgG antibody, which carries it through the placenta or insulin is forced through the placenta by high perfusion (6,7). Diabetic fetopathy is thought to be the result of fetal hyperinsulinemia (1)(2)(3)(4)(5)(6)(7)(8)(9). Thus, our treatment must be designed to normalize maternal blood glucose concentrations without the use of exogenous insulins that cross the placenta.…”
Section: Rationale For the Use Of Non-immunogenic Insulins Duringmentioning
confidence: 99%
“…Only negligible amounts of maternal insulin and insulin analogs cross the placental barrier at therapeutic concentrations (18,19,20). This explains the lack of correlation between maternal venous insulin concentrations and umbilical venous insulin concentrations (20,21).…”
Section: :5mentioning
confidence: 99%